O6 Good to go: enhancing care transfers from hospital to home for older people with complex needs. (17th November 2016) - Thomas, B; Baillie, L; Martin, F; Sykes, S; Scotter, J
Abstract : Background: Care transfers from hospital to home for older people with complex needs should be person-centred with effective multidisciplinary teamwork (Bolsch et al, 2005), but are a challenge nationally. The Good to Go simulation-based training course was developed to: draw upon shared experience and knowledge to promote best practice for safe care transfers across a range of settings enhance discharge planning skills including effective communication, assessment and evaluation of needs and the ability to work within a multi-agency, multi-professional arena. Method: Informed by best practice review, local scoping and staff perspectives, the course design reflected a patient journey from hospital to community care, aimed at health/social care professionals with roles involving care transfers of older people. Consisting of mixed-modality simulation activities including use of actors and the opportunity for learners to experience the challenges older people face in performing everyday tasks through wearing a suit which replicates physical constraints i.e. reduced movement, vision and hearing. Results: 49 multi-agency staff attended. Evaluation was based on Kirkpatricks (1994) model consisting of pre-course (n = 44) and post-course (n = 47) questionnaires and semi-structured interviews (n = 9) exploring perceived application and impact on practice. Aims were achieved with positive evaluation. Pre-course, 30 (68%) participants reported difficulty with transferring or receiving the care of a patient with complex needs. Post-course, 44 (91%) intended to make changes to their practice. The inter-professional learning enabled building of professional relationships and improved understanding of each others roles. Further results presented at conference. Conclusion: Equipping staff with the knowledge and skills to facilitate high quality care transfers for older people in todays challenging context, this inter-professional course strengthens team working across hospital and community settings. It could be transferred to other settings. A challenge is that staff turnover across London is high but staff could transfer learning to new organisations.